식물의 생장 및 발달과정에서 Glycogen synthase kinase 3 (GSK3) 유전자의 역할 - 류호진(Hojin Ryu) (Journal of plant biotechnology, 2015)
The biological roles of glycogen synthase kinase 3 (GSK3) proteins have long been extensively explored in eukaryotic organisms including fungi, animals and plants. This gene family has evolutionary well conserved kinase domain and shares similar phosphorylation properties to their substrate proteins. However, their specific biological roles are surprisingly distinct in different organisms. GSK3s play key role in key regulating the cytoskeleton and metabolic processes in animal systems, but plant GSKs are involved in quite different processes, such as flower development, brassinosteroid signaling, abiotic stresses, and organogenesis. In particular, recent studies have reported the critical multiple functions of BIN2 and its related paralogues plant GSK3s during organogenesis via connecting hormonal or developmental programs. In this review, we outline the recent understanding in the versatile functions related in physiological and biochemical relevance, which are mediated by plant GSK3s in various cellular signaling.